Integrating Smartphone Apps During Differentiated Teaching: Promoting Increased Student Engagement and Performance in Team Sports Activities in Middle School Physical Education - Ega Trisna Rahayu; Edi Setiawan; Rolly Afrinaldi; Kamal Prihandani; Rina Syafrida; Mochammad Ikhsanul Al Raffi; Amayra Tannoubi; Allabergan Sharipov; Adang Suherman; Ferman Konukman (Physical Activity and Health)
This study aims to investigate the effects of smartphone apps (SA) which were integrated with the differentiated teaching model (DTM) on study engagement (SE), and games performance (GP) students in physical education (PE) classes. This study adopted a 9-week experimental method. Sixty males, and females students were assigned to the SA integrated DTM group (n = 30, male = 15; female = 15), and traditional teaching (TT) (n = 30, male = 15; female = 15). SE and GP were measured at the pre-test, mid-test, and post-test stages. The results of the 2-way repeated measure (RM) ANOVA analysis showed that there were significant main effects of time, teaching, and interaction on SE related to vigor (p < 0.001), dedication (p < 0.001), and absorption (p < 0.001). There were significant main effects of time, teaching, and interaction on GP with aspects of base (p < 0.001), adjust (p < 0.001), decision-making (p < 0.001), skill execution (p < 0.001), support (p < 0.001), cover (p < 0.001), and guard/mark (p < 0.001). We conclude that the current study on SA integrated during DTM is methodologically effective towards improving SE, and GP of male and female students in PE classes.